2019
DOI: 10.35940/ijrte.c4314.098319
|View full text |Cite
|
Sign up to set email alerts
|

Stock Market Prices Prediction using Random Forest and Extra Tree Regression

Abstract: Prediction of Stock price is now a day’s an existing and interesting research area in financial and academic sectors to know the scale of economies. There did not exists any significant set of rules to estimate and predict the scale of share in the stock exchange. Many evolutionary technologies are existing such as technical, fundamental, time, statistical and series analysis which help us to attempt the prediction process, but none of the methods are proved as reliable and accurate tool to the society in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 4 publications
1
13
0
Order By: Relevance
“…In terms of computational speed and power, there are reasons why Random Forest (RF) may be faster at performing calculations to predict Bitcoin prices compared to Long Short-Term Memory (LSTM). The Random Forest algorithm is based on a collection of relatively simple decision trees [32], whereas LSTM involves a more complex neural network with multiple layers and more complicated connections [33]. Computations in RF usually involve making simple decisions on each tree, which may take less time Ì 269 than LSTMs and have to go through many layers of neurons and more complicated mathematical computations.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of computational speed and power, there are reasons why Random Forest (RF) may be faster at performing calculations to predict Bitcoin prices compared to Long Short-Term Memory (LSTM). The Random Forest algorithm is based on a collection of relatively simple decision trees [32], whereas LSTM involves a more complex neural network with multiple layers and more complicated connections [33]. Computations in RF usually involve making simple decisions on each tree, which may take less time Ì 269 than LSTMs and have to go through many layers of neurons and more complicated mathematical computations.…”
Section: Discussionmentioning
confidence: 99%
“…Random forest constructs numerous versions of These tree predictions are combined with a majority vote to get the final projection. As a consequence, over-fitting is reduced, and predicted accuracy is improved [27]. An overview of how the algorithms work is depicted in Figure 2.…”
Section: Random Forest Modelmentioning
confidence: 99%
“…Khaidem et al [2] used a random forest algorithm to predict the direction of stock market prices, achieving an accuracy for some stocks to about 85-90%. Polamuri et al [1] presented a methodology for predicting stock prices using random forest and extra tree regressions algorithms. The authors conclude that machine learning algorithms can be used for estimating the prices of stocks.…”
Section: Use Of Machine Learning Algorithmsmentioning
confidence: 99%
“…Khaidem et al [2] used the algorithm to achieve an accuracy of 85-90% for predicting the direction of stock market prices. Polamuri et al [1] presented a methodology for predicting stock prices using the random forest and extra tree regressions algorithms. Kumar et al [13] found that the random forest algorithm achieved the highest prediction accuracy among several supervised machine learning algorithms, including decision trees and support vector machines, for larger datasets.…”
Section: Random Forestmentioning
confidence: 99%